Biospeciation of Cr(III) Nutritional Supplements in Biological Fluids - Safitri, Anna; Levina, Aviva; Lay, Peter A. (Makara Journal of Science, 2017)
Metal ion speciation in various biological systems has been extensively studied to elucidate its biological role and the toxicity of the element of interest. In the present study, chromium speciation was performed by reacting Cr(III) nutritional supplements [Cr(pic)3], where pic = 2-pyridinecarboxylato(-), and a Cr(III) propionate complex, [Cr3O(OCOEt)6(OH2)3])+, in calf serum. Cr(III) complexes in serum were fractionated using size-exclusion chromatography, and the Cr(III) concentrations in each fraction were determined using graphite furnace atomic absorption spectroscopy. The results showed that Cr(III) bound to both high-and low-molecular weight serum fractions. While Cr(III) was mainly bound toalbumin or transferrin, unknown low-molecular-weight serum fractions were also important in Cr binding. The Cr(III) distribution in serum fractions was found to be time-dependent.